2015
DOI: 10.1016/j.neuropsychologia.2015.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Eyetracking of social preference choices reveals normal but faster processing in autism

Abstract: People with Autism Spectrum Disorder (ASD) have been reported to show atypical attention and eva luative processing, in particular for social stimuli such as faces. The usual measure in these studies is an explicit, subjective judgment, which is the culmination of complex-temporally extended processes that are not typically dissected in detail. Here we addressed a neglected aspect of social decision-making in order to gain further insight into the underlying mechanisms: the temporal evolution of the choice. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
(54 reference statements)
0
6
1
Order By: Relevance
“…It is noteworthy that our data appear inconsistent with an earlier eye‐tracking study that observed no differences between ASD and NT groups in terms of gaze cascade trajectories or social choice behaviors (Gharib, Mier, Adolphs, & Shimojo, 2015). In context, however, the differences between this study and our own may outweigh the similarities.…”
Section: Discussioncontrasting
confidence: 99%
“…It is noteworthy that our data appear inconsistent with an earlier eye‐tracking study that observed no differences between ASD and NT groups in terms of gaze cascade trajectories or social choice behaviors (Gharib, Mier, Adolphs, & Shimojo, 2015). In context, however, the differences between this study and our own may outweigh the similarities.…”
Section: Discussioncontrasting
confidence: 99%
“…This is reminiscent of a series of experiments conducted in patients with autism. During social scene observation, toddlers with autism are less focused on eyes in comparison with neurotypical toddlers ( Constantino et al, 2017 ), but they can be faster at identifying facial information compared with typically developed individuals ( Gharib et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…A small amount of literature also addresses the needs of autistic research participants who are Deaf or deaf 102 . Instruments that rely on gaze or eye contact might prove particularly problematic for people with autism, thus requiring modification 103 . Instrument choice is a methodological decision but can also be considered an ethical choice, given that inappropriate instruments may mischaracterize people with autism 104 …”
Section: Research Design Strategiesmentioning
confidence: 99%